The effect of work stress, organisational culture and work environment on employee performance at PT Otani - Calvin Calvin; Cut Fitri Rostina; Rita Rita; Belaminov Br Sirait (Institute of Computer Science (IOCS), 2023)
The purpose of this research to know and explain the effect of work stress, organisational culture and work environment on employee performance. The research is descriptive quantitative type, with explanatory nature. 250 employees at PT Otani are the population in the study. The sampling technique used the Slovin formula which resulted in a sample of 154 people. Interview techniques, questionnaires and documentation studies were conducted to obtain research data. Data analysis methods are multiple linear regression, coefficient of determination test, partial test and simultaneous test. The research resulted in Work Stress, Organisational Culture and Work Environment both independently and simultaneously affecting the performance of employees of PT Otani. The variation of independent variables on the dependent variable is 43.6%, the remaining 56.4% is explained by other factors not included in this study, such as leadership, work conflict, compensation, and others.